"Geography of silence": characteristics of the spatiality of deaf people over time (PerCursos, 2023)
The absence of geographical studies on the spaces of minorities, including the deaf, is a clear gap in the analysis of the current Brazilian city. This article aims to present some characteristics of the spatiality of the deaf over time through a literature review on the history of these individuals and the development of a brief historicization. Through this, it will be possible to understand that the deaf were long confined to their homes, deaf clubs, and schools, and in recent times, there has been a progressive effort to promote true inclusion of the deaf and hearing-impaired in the city. In the late twentieth century, the deaf community has been organizing and strengthening socially through accessibility and inclusion policies, which have become prominent in local, national, and international debates. Thus, the mobilization of this group for their rights is expressed on various fronts, including the demand to live in the city. Unlike the realities faced by the deaf in the past, where deafness was considered a disabling condition, exacerbating the social exclusion of this group, it is possible to understand, through the historical context presented, the pursuit of identification and overcoming the barriers that still exist in cities, hindering their mobility and impacting their freedom to move and pursue their desires. This article constitutes a segment of a doctoral research, with its central theme being the discussion of the city as an deficient space to meet the needs of deaf individuals in their multifaceted aspects.
Keywords: deaf geography; deaf community; socio-spatial inclusion; city